STRATEGI JEPANG DALAM EKSPOR MOBIL TOYOTA DI INDONESIA TAHUN 2017-2019 - Ilmiyatul Khairi; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study examines Japan's Strategy in Exporting Toyota Cars in Indonesia in 2017-2019 which aims to expand the Toyota market in Indonesia and strengthen bilateral relations between these two countries. Indonesia as the country with the largest economy in Southeast Asia, the Indonesian automotive industry has become an important pillar in the country's manufacturing sector because many world-renowned car companies open car manufacturing factories or increase their production capacity in Indonesia. The author collects data from books, academic journals, official documents, theses and sources from the internet related to research issues on Japan's strategy in toyota car exports in Indonesia. The author uses the perspective of liberalism and the level of analysis of the nation state. While the theory used in this theory is the theory of competitive advantage of Michael E. Porter. The results of the study show that Japan's strategy to expand the automotive market in Indonesia by building factories in Indonesia to strengthen the automotive industry and improving national macroeconomic indicators and efforts to continue to improve the quality of infrastructure in the transportation sector. Japan also reduced the cost of customs tariffs in accordance with the IJEPA agreement, and there are three classifications, namely fast-track, normal track, and exceptions by installing emergency and safeguard measures to prevent possible negative impacts on the domestic industry. About 35% of Indonesia's import duty tariff posts will be reduced to 0%, meanwhile Japan will reduce about 80% of its tariff posts. Keywords : Japan’s Strategy, Toyota Car Exports, IJEPA, Automotive Industry